Techniques for studying the impact of natural enemies - Luck, R.F. (California Univ., Riverside CA 92521 (USA). Dept. of Entomology) (Malaysian Plant Protection Society, 2013)
Six general experimental approaches have been used to evaluate the efficacy of either indigenous or introduced natural enemies. These include (1) introduction and augmention, (2) use of cages and barriers, (3) removal of natural enemies, (4) prey enrichment, (5) direct observation, and (6) physical, chemical and biochemical evidence of natural enemy feeding. Each of these approaches will be discussed, with examples, and the appropriateness and limitations of each will be considered within the constraints of the biology of the organisms involved, the questions being addressed and the context and economic importance of the problem